2007
DOI: 10.1002/lt.21354
|View full text |Cite
|
Sign up to set email alerts
|

Biliary complications following liver transplantation in the model for end-stage liver disease era: Effect of donor, recipient, and technical factors

Abstract: Biliary complications remain a significant problem following liver transplantation in the Model for End-Stage Liver Disease (MELD) era. We hypothesized that donor, recipient, and technical variables may differentially affect anastomotic biliary complications in MELD era liver transplants. We reviewed 256 deceased donor liver transplants after the institution of MELD at our center and evaluated these variables' association with anastomotic biliary complications. The bile leak rate was 18%, and the stricture rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
149
3
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(163 citation statements)
references
References 27 publications
(43 reference statements)
9
149
3
2
Order By: Relevance
“…The University of Michigan reviewed 256 OLTs performed after the institution of the Model for End-Stage Liver Disease and found that longer warm ischemic time was the only independent risk factor after multivariate analysis for the development of biliary leaks. 16 The presence of biliary casts was not evaluated in that study. Prolonged warm ischemic time has also been associated with irreversible bile duct damage and poorer outcomes in NHBD grafts.…”
Section: Discussionmentioning
confidence: 95%
“…The University of Michigan reviewed 256 OLTs performed after the institution of the Model for End-Stage Liver Disease and found that longer warm ischemic time was the only independent risk factor after multivariate analysis for the development of biliary leaks. 16 The presence of biliary casts was not evaluated in that study. Prolonged warm ischemic time has also been associated with irreversible bile duct damage and poorer outcomes in NHBD grafts.…”
Section: Discussionmentioning
confidence: 95%
“…[11][12][13] Although many large series have reported the overall rates of postoperative graft nonfunction; vascular thromboses; and biliary, infectious, and hemorrhagic complications, 5,11,12,[14][15][16][17][18][19] neither the specific management nor the effects of these complications on graft and patient survival are described. This study represents the largest contemporary singlecenter experience to report the scope of reoperative complications after primary liver transplantation and their associations with graft and patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Biliary complications occur in 10%-40% of patients after LT [37][38][39][40] , with major incidence in patients with partial LT [41][42] . Complications include BSs, bile leakage (BL), biliary stones and bilomas.…”
Section: Treatment Of Biliary Complicationsmentioning
confidence: 99%
“…BS is a common problem after LT with a reported incidence of 10%-35% [37][38][39][40] . Anastomotic BS is usually related to scar tissue and retraction at the suture site [41][42] .…”
Section: Biliary Strictures (Bs)mentioning
confidence: 99%
See 1 more Smart Citation